Concession, intensité assertive et argumentation – étude comparée de deux constructions concessives en anglais - Stéphane Gresset; Gérard Mélis (Anglophonia)
The main purpose of this article is to examine the difference between two concessive constructions in contemporary English: the clause introduced by ALTHOUGH (ALTHOUGH+P) in initial position before the main clause and MAY-BUT. This study takes into account, not only the well-known characteristic features of concession as an argumentative process (the deconstruction of an inferential relation between two propositions, and intersubjectivity), but also another feature, namely the degree of assertiveness assigned to the propositional contents involved in the concessive process.By comparing examples where these two constructions are interchangeable and others where, on the contrary, only one construction is acceptable, we hypothesize that, if the purpose of both these concessive constructions is clearly to highlight one propositional content, the degree of assertiveness associated with that content varies depending on the choice of construction. In other words, and this is what we plan to demonstrate through a detailed analysis of contextualized examples, these two constructions implement different argumentative strategies.